The Correlation Between Students’ Vocabulary Mastery and Reading Comprehension at the Eighth-Grade Students of SMPN 2 Sojol - Andi Naniwarsih; Ratna Ningtyas (Universitas Muhammadiyah Palu, 2023)
The research aims to determine whether there was a correlation between vocabulary mastery and reading comprehension. The study used a simple random sampling technique, namely, taken 30 students in class VIII B. However, the correlation criterion between 0.60 and 0.80 was considered very high. The researchers concluded that rxy = 0.797 and N 30 at a 5% correlation significance is 0,361. Therefore, based on the Pearson Product Moment formula, compared to the rtable, the study found that rcount higher than rtable (0.361), the average Ho was rejected, and Ha was accepted. To sum up, the final results exhibited a correlation between students' vocabulary mastery and reading comprehension.